2022
DOI: 10.3390/ijms23020857
|View full text |Cite
|
Sign up to set email alerts
|

Human Amnion-Derived Mesenchymal Stromal Cells: A New Potential Treatment for Carbapenem-Resistant Enterobacterales in Decompensated Cirrhosis

Abstract: Background: Spontaneous bacterial peritonitis (SBP) is a severe and often fatal infection in patients with decompensated cirrhosis and ascites. The only cure for SBP is antibiotic therapy, but the emerging problem of bacterial resistance requires novel therapeutic strategies. Human amniotic mesenchymal stromal cells (hA-MSCs) possess immunomodulatory and anti-inflammatory properties that can be harnessed as a therapy in such a context. Methods: An in vitro applications of hA-MSCs in ascitic fluid (AF) of cirrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Alternative immune therapies that can decrease bacterial proliferation are under evaluation [ 35 , 36 , 50 , 51 ]. Regenerative medicine holds potential for addressing this issue by modulating the expression of specific immunological targets, which can reduce bacterial load and restore homeostasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternative immune therapies that can decrease bacterial proliferation are under evaluation [ 35 , 36 , 50 , 51 ]. Regenerative medicine holds potential for addressing this issue by modulating the expression of specific immunological targets, which can reduce bacterial load and restore homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has recently shown, in vitro, that by co-culturing hA-MSCs with infected ascites obtained from patients with cirrhosis with refractory ascites, these stem cells exhibit antibacterial properties, modulate inflammatory cytokine pathways [ 32 , 33 , 34 ], stimulate the production of anti-inflammatory cytokines, and mediate a balanced immune response toward a resolution of the infection [ 35 ]. hA-MSCs have been found to promote anti-inflammatory M2 macrophage polarization without affecting the phagocytosis activity of macrophages and NK cells, reduce C3a complement protein and Ficolin-3 concentrations during the course of infection, and significantly decrease the proliferation of common carbapenem-resistant Enterobacterales strains responsible for SBP, including E. coli and Klebsiella pneumonia [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential approach is human amniotic mesenchymal stromal cell (hA-MSC) treatment. One in vitro study found hA-MSCs added to ascites fluid could significantly reduce the proliferation of both bacterial strains at 24 h as well as affect M1/M2 polarization, C3a complement protein, and ficolin 3 concentrations during the course of infection in a strain-dependent manner [101]. Validation of an in vivo model is warranted for future hA-MSC application in treating ascites infected with carbapenemresistant bacteria [101].…”
Section: Other Novel Therapeutic Strategiesmentioning
confidence: 99%